2015
DOI: 10.1108/ss-06-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

Home owners and developers relationships: exploring the cordiality factor

Abstract: Purpose – The cordiality of the relationship between home owners and house developers is significant in the house building sector. This plays a key role in meeting needs, expectations and overall satisfaction. Home owners’ satisfactions are very often dependent on their encounters and experiences with the building organisations they deal with. The purpose of this paper is to explore home owners’ satisfaction to the quality of their new homes by investigating the relationships between them and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Real estate entrepreneurs should heed buyers’ preferences by injecting contemporary architectural design in order to spur sophistication of discerning homebuyers and investors. It is suggested that the developers apply a customer survey to determine their needs and expectations as well as providing a different standard of quality performance with other firms (Rotimi et al , 2015). Paradoxically, many property developers argued that the implementation should be accompanied with high creativity to accurately gauge the development pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real estate entrepreneurs should heed buyers’ preferences by injecting contemporary architectural design in order to spur sophistication of discerning homebuyers and investors. It is suggested that the developers apply a customer survey to determine their needs and expectations as well as providing a different standard of quality performance with other firms (Rotimi et al , 2015). Paradoxically, many property developers argued that the implementation should be accompanied with high creativity to accurately gauge the development pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Lee and Ng (1996) add that, through up-to-date-information on homebuyers’ preferences, business success of housing developers can be achieved. Tapping the exact segment of the housing market warrants housing developers to study consumer’s preferences and tastes via feasibility research and use of a scientific approach (Jaafar et al , 2015; Miles et al , 2000; Rotimi et al , 2015). The findings will be useful for improving the design and development of future housing projects while implicitly providing competitive advantage in today’s property market environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additional studies have shown that the production process, product handover, and post-occupancy customer services have a significant impact on how customers perceive and evaluate the quality of a building project [7,8,14,22]. The occurrence of defects after the product handover and poor customer service can greatly impact customer satisfaction.…”
Section: Definition Incidence and Relationship With Managerial Indicatorsmentioning
confidence: 99%
“…Throughout this period of time numerous other academics and practitioners have researched both defects, snagging, quality and rework within the UK house building industry including Sommerville and McCosh (2006), ), Craig (2007 Sommerville (2008) Auchterlounie (2009) and, Rotimi et al (2014 with the majority of these focusing on defects in terms of numbers created. It is generally acknowledged that the number of defects at the completion or handover stage (completion of the end-product) of a building appears to have a positive or negative influence on the satisfaction of the client or customer, however over the last two decades the construction industry has become obsessed with the attainment of quality through the measurement and use of defects as a proxy.…”
Section: The Literature the Concept Of Quality And Quality In House Bmentioning
confidence: 99%